KEPEMIMPINAN, KOMUNIKASI DAN KEPUASAN KERJA KARYAWAN DI VILLA THE LAYAR SEMINYAK - Ni Made Putri Aryawati; I Nengah Aristana (Universitas Triatma Mulya, 2020)
This study aims to determine the effect of leadership and employee satisfaction at Villa The Layar Seminyak. This research is a quantitative study that describes and explains how the influence of leadership and communication on employee job satisfaction at Villa The Layar Seminyak. The population used was 150 employees and the sample used was 60% of the total population or as many as 90 respondents. Testing instruments using the validity and reliability test. Data analysis techniques used multiple linear regression, the classic assumption test, the coefficient of determination, and the t test. The results showed that (1) leadership had a positive effect on employee job satisfaction at Villa The Layar Seminyak with a value of 0.501, (2) communication had a positive effect on employee job satisfaction at the Villa Seminyak Screen with a value of 0.143, (3) the magnitude of the influence of leadership and communication to job satisfaction of employees at Villa The Layar Seminyak by 56.8%, (4) leadership is the most dominant influence on employee job satisfaction at Villa The Layar Seminyak with a value of 0.595.